(untitled) (Journal of the College of Basic Education, 2022)
During the crude oil production, water-in-oil stable emulsions may be created. Water which is naturally present in oil reservoirs mixes with crude oil to form very stable emulsions due to very high shear rates and zones of turbulence encountered at the wellhead and pipe of production. The formation of these emulsions is generally caused by the presence of resins, asphaltenes, wax and naphtenic acid which play the role of "natural emulsifiers. The aim of this study was to focus on some important factors in the formation and stabilize crude oil/water emulsions. These factors are the water content, which varies from oil field to another and to understand its role in the Stability of the emulsion, which vary depending on the oil fields. Another factor is the temperature at which the physicist has a role in a large non-oil emulsions Stability. The study deals with the effect of water content and temperature on the stability of crude oil emulsion. The emulsion was prepared by mixing the crude oil and desired content of water and shaking by hand. The volume percent of water were studied in this paper to the total volume of crude oil emulsion (10, 20, 30, 40, 50, 60) and temperature were (20, 30, 40, 50) OC. The results showed that, the emulsion stability decrease with increase water concentration. Change in temperature had a significant effect where the higher temperature became unstable emulsions Key words : emulsion, crude oil / water emulsion stability